A Generalization of the Krätzel Function and Its Applications. (26th January 2017) - Dernek, Neşe; Dernek, Ahmet; Yürekli, Osman
Abstract : In this paper, we introduce new functions Y ρ, r ν ( x ) as a generalization of the Krätzel function. We investigate recurrence relations, Mellin transform, fractional derivatives, and integral of the function Y ρ, r ν ( x ) . We show that the function Y ρ, r ν ( x ) is the solution of differential equations of fractional order.